Mise en scène e corpo no cinema no século XXI: reflexões críticas a partir de Apichatpong Weerasethakul e Henrique Nogueira Neme - Neme, Henrique Nogueira (2021)
This study stems from initial discussions on staging in cinema (mise en scène) and its resulting problematizations, moves on to theories addressing this topic in the transition from classic cinema to modern cinema, and examines how mise en scène is approached in the 21st century. Based on this initial mapping, the research carries out a critical review of the notion of mise en scène in light of the independent cinema of the 2010s by examining sequences from the films Uncle Boonmee Who Can Recall His Past Lives (2010), by Apichatpong Weerasethakul, and Hermético (Hermetic, 2017), by Henrique Nogueira Neme. Thus, a type of relationship established in fiction cinema, in the form of “sensory narratives” (GONÇALVES, 2014) can be identified, in which the relations between images do not develop a narrative that operates through chains of meaning providing a dramatic structure with plot, twists, climaxes, and conclusions. In the “sensory narratives,” the images are exposed in an apparently autonomous fashion, because they are explored in their visual potencies as they are presented to the viewer. A story that is produced, told, and organized in a series of closed meanings gives way to a type of work presented as a becoming that provokes sensations and affections. These are expressions that work the intensity of images—through the articulation of shots and their respective framing—and evince a relationship with the body, which comprises the characters and other elements that are part of the landscape, which are present in the visible field of the cinematographic image. The theoretical structure is interdisciplinary, and includes communication, art, and philosophy. The research draws on Paul Virilio (2002) and Luiz Carlos Oliveira Júnior (2014) to conceptualize the problematizations of the mise en scène in cinema and the aesthetics that are built by exploring image intensities. Phillipe Dubois (2004) and Christine Mello (2008) offer the possibility of basing the research on their theories of communication, more specifically media theories with an emphasis on the audiovisual field. Mônica Toledo Silva (2005, 2011) and Lucia Santaella (2018) present concepts that allow us to examine the body in the cinematographic image and the extended body in the elements that make up the cinematographic work. Osmar Gonçalves (2014) and Hans Ulrich Gumbrecht (2010, 2011) offer the groundwork, respectively, for “sensory narratives” in cinema and its forms of presentation. The analysis of cinematographic works, based on the problematizations of mise en scène, draws on the extremities approach developed by Christine Mello